Segmenting cultural consumers in the experiential perspective: does it make sense? - Emanuela Conti; Massimiliano Vesci; Arja Lemmetyinen; Tonino Pencarelli (Italy, 2022)
The main objective of this study is to cluster museum visitors (Wedel and Kamakura, 2002) using the experiential dimensions of Pine and Gilmore (1999). To attain this goal, first, an exploratory factor analysis has been performed and, second, adopting the factorial scores herein obtained, a cluster analysis with K-Means technique has been conducted on a sample of Italian and Finnish museum visitors. Data has been collected through a survey via face-to-face interviews on a sample of visitors to the National Gallery of the Marche, a state-run museum focused on the Renaissance period, and to the Turku Art Museum, an art museum located in Turku, the old capital of Finland. The empirical research revealed six different clusters of visitors; some clusters may be considered the "classic" museum visitors who are mainly interested in the edutainment and esthetic dimensions of the museum experience, while other clusters represent the "new targets" who are not interested in edutainment or less interested in all the dimensions of the visiting experience. The main managerial implication for museums consists investing resources in all kinds of experiences to satisfy heterogeneous targets. Theoretical background and objectives Visitor experience has recently become one of the major topics explored in the cultural heritage management (CHM) literature, in visitor studies, but museum experience segmentation is still under-researched. The literature has shown that the motivation of the visit is not positively correlated with the depth/intensity of the experience, therefore it becomes interesting to understand not so much the reasons for visiting a museum but the visit experience or the dimensions of the experience; the visitor experience in affected by individual attributes (level of education, exposure to art during childhood, level of interest for particular cultural products) and the museum or context attributes (services, location, lighting, visitor's involvement, the technologies offered) (Poria et al., 2006). For example, there are six criteria for a desirable leisure experience in museums (Chen, 2012): engaging in social interaction; doing something worthwhile; feeling comfortable and at ease in one's surroundings; being challenged by new experiences; having the opportunity to learn; and participating actively. According to other Authors, the attraction factors of a museum are based on push and pull motivations (Yoon and Uysal, 2005) and most visitors are driven by push factors (e.g. relaxation) and seek new experiences and the possibility of learning new things. It seems that museum visitors do not search knowledge enrichment but recreation, entertainment, and social interaction (Nowacki, 2010). Poria et al. (2009), stressed the importance of customized information, emotional involvement, and a strong connection with the cultural location. In addition, visitor experience and engagement is today enhanced by the use of technologies (Marthy, 2007). In general, the literature on measurement of museum experience is still scarce and museums still do not measure this important factor which is fundamental to improve their offer and visitors'
Marketing 4.0: the multi-channel challenges: XVI SIM Conference, Proceedings